On osculating, normal and rectifying bi-null curves in ℝ63. Issue 1 (2nd January 2017) - Uçum, Ali; Sakaki, Makoto; İlarslan, Kazim
Abstract: In this paper we give the necessary and sufficient conditions for bi-null curves in ℝ 6 3 to be osculating, normal or rectifying curves in terms of their curvature functions.